PENERAPAN EGG TRAY UNTUK MEREDUKSI TINGKAT KEBISINGAN PADA RUANG KELAS MTs ISLAMIYAH TANJUNG KASAU - Suci Ramadhani Harahap; Mulkan Iskandar Nasution; Nazaruddin Nasution (Universitas Riau, 2023)
Noise can be reduced by using materials that can dampen and absorb sound. Sound absorbing materials have an important role in room acoustics. This study aims to apply egg trays to the walls of MTs Islamiyah Tanjung Kasau classrooms. The study was conducted by measuring the noise level before and after the implementation of the egg tray on open and closed doors and windows in the MTs Islamiyah Tanjung Kasau classroom at 20 different points. The source of the sound comes from the sound generated by the activity of vehicles on St. Sei Langgei Perk Village. Tanjung Kasau during school operating hours. The tool used to measure noise levels in this study is a sound level meter (SLM). Data processing uses Surfer Golden V16 Software to create a contour map of sound distribution. The noise level generated in the classroom before the implementation of the egg tray when the doors and windows were open and closed was 61.39 dB and 59.41 dB. These results did not meet the standards in accordance with KEPMENLH No. 48 of 1996 concerning the Noise Level Standard for Schools, which is 55 dB. Then an acoustic absorbing material was added to the classroom using egg tray material to reduce noise in the MTs Islamiyah Tanjung Kasau classroom. The noise level after the application of the egg tray in open condition is 53.47 dB, in closed condition is 49.99 dB.